2020
DOI: 10.15766/mep_2374-8265.11032
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Critical Care Curriculum for the Third-Year Internal Medicine Clerkship

Abstract: Introduction: A majority of residents provide care for critically ill patients, yet only a minority of medical schools require ICU rotations. Therefore, many medical students enter residency without prior ICU experience. The third-year internal medicine (IM) clerkship at our institution's Veterans Affairs Medical Center (VAMC) provided an opportunity for medical students to rotate through an open ICU as part of their inpatient ward rotation. Prior to March 2019, no structured critical care curriculum existed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…A total of 2,435 results were returned from the initial search between the 5 databases, of which 17, published between 1983 and 2020, were selected for full-text review ( 6 , 20 34 , 36 ). The second search performed in August 2021 returned 2 further studies published in 2021 ( 19 , 35 ). The findings of these 19 studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 2,435 results were returned from the initial search between the 5 databases, of which 17, published between 1983 and 2020, were selected for full-text review ( 6 , 20 34 , 36 ). The second search performed in August 2021 returned 2 further studies published in 2021 ( 19 , 35 ). The findings of these 19 studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies, 9 (47.4%) involved anesthesia ( 21 , 23 25 , 28 – 32 ), 8 (42.1%) intensive care medicine ( 6 , 19 , 20 , 26 , 27 , 33 35 ) and 2 (10.5%) a combination of both disciplines ( 22 , 36 ). The primary research focus was on the assessment instrument and on student learning in 9 ( 22 26 , 28 – 30 , 36 ) and 7 ( 19 21 , 27 , 32 , 33 , 35 ) studies respectively. The remaining 3 studies had equal research focus on learning and the assessment tool.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations